Applying 3D Polygonal Mesh Watermarking for Transmission Security Protection through Sensor Networks. (9th January 2014) - Hu, Roland; Xie, Li; Yu, Huimin; Ding, Baocang
Abstract : Although many research works have been carried out in the area of transmission 3D data through sensor networks, the security issue of transmission remains to be unsolved. It is important to develop systems for copyright protection and digital right management (DRM). In this paper, a blind watermarking algorithm is proposed to protect the transmission security of 3D polygonal meshes through sensor networks. Our method is based on selecting prominent feature vertices (prongs) on the mesh and then embedding the same watermark into their neighborhood regions. The embedding algorithm is based on modifying the distribution of vertex norms by using quadratic programming (QP). Decoding results are obtained by a majority voting scheme over neighborhood regions of these prongs. Assuming that cropping cannot remove all prongs, we can achieve robustness against the cropping attack both theoretically and experimentally. Experiments indicate that the proposed method is also robust against noise, smoothing, and mesh simplification. The proposed method has provided a solution for 3D polygonal watermarking which is potential to withstand a variety of attacks.